3D visualization and quantitative analysis of human erythrocyte phagocytosis. (13th September 2016) - Stachurska, Anna; Król, Teodora; Trybus, Wojciech; Szary, Karol; Fabijańska‐Mitek, Jadwiga
Abstract: Since the erythrophagocytosis of opsonized erythrocytes is investigated mainly by calculating the phagocytic index using subjective light microscopy evaluation, we present methods for the quantitative and qualitative analysis of human cell erythrophagocytosis. Erythrocytes from two storage periods were used. Using Imaris software, we were able to create a three‐dimensional model of erythrophagocytosis. The use of microscopy instead of cytometry revealed a significantly higher number of monocytes and erythrocytes that appeared active in phagocytosis. Spatial reconstruction allowed for detailed analysis of the process by precisely locating erythrocytes in phagocytes. Additionally, a technique of sequential image registration using Nis Elements software allowed for observation of the course of phagocytosis over a range of time intervals. This in vitro research may be helpful for understanding the cellular interactions between monocytes and erythrocytes. The cytometric method—being relatively rapid, sensitive, and specific—can serve as an alternative technique to microscopy in the quantitative analysis of erythrophagocytosis. This allows us to avoid counting the erythrocytes nonspecifically attached to monocytes and gives objective results.